Local Property Tax Reform and Municipality Spending Efficiency - António Afonso; Ana Venâncio (Center for Economic Studies and ifo Institute (CESifo), 2022)
We investigate the effect on municipality spending efficiency of a local property tax reform, which reduced in 2008 the upper limit of the property tax. We compute municipality efficiency scores via data Envelopment Analysis (DEA) from 2005 to 2011, and then we rely in a panel data set to estimate how the tax reform affected the efficiency scores. Results of the analysis show that average input efficiency scores declined from 0.575 before the tax reform to 0.488 after the tax reform. This change was transversal to municipalities that reduced the municipal property tax (IMI) and to the ones that maintained the tax rate. In addition, the IMI reform is linked to higher efficiency scores. In other words, the reduction in efficiency ends up being smaller for the municipalities that decreased the IMI tax rate.
Keywords: C14; C23; H11; H21; H50; 330; public spending efficiency; local government; data envelopment analysis (DEA); local property tax reform